Presentation and Analysis of “Three Teachings Syncretism” in Song and Jin Poetry and Its Modern Significance - Lei, Enhai (Religions, 2025)
The “Three Teachings Syncretism” (sanjiao heyi, 三教合一), i.e., the integration of Confucianism, Buddhism, and Daoism, represents an important religious philosophy in ancient China. This article aims to analyze how this ideology is presented and expressed directly in Song and Jin poetry, along with its modern value and significance. To achieve the research objectives, the paper isolates related poems from the Complete Song Poetry and Complete Liao Jin Poetry as the research objects. First, it organizes and classifies the relevant poems through the ways in which the idea of “Three Teachings Syncretism” is presented. Second, it examines the reasons behind this phenomenon, including the intellectualization of poetry and the Confucian academic background of Buddhist monks and Daoist priests. Thirdly, it explores the value and significance of this thought for modern China, showcasing the inherent diversity, inclusiveness, and harmony in Chinese culture.